Rights of disabled people in Great Britain and Northern Ireland : A report on the United Nations Convention on the Rights of Persons with Disabilities by (the United Kingdom) Great Britain and Northern Ireland.: A report on the United Nations Convention on the Rights of Persons with Disabilities by (the United Kingdom) Great Britain and Northern Ireland. (2018) - Unknown
No abstract available